Measurements of Spectrally Averaged Absorptivity and Emissivity for a Selective Solar Absorber in High Vacuum Under Direct Solar Illumination. (August 2020) - Alessandro, C D'; De Maio, D; De Luca, D; Musto, M; Di Gennaro, E; Rotondo, G; Dalena, D; Russo, R
Abstract: The innovative ultra-high vacuum technology applied to solar thermal flat panels, allows to reach high operating temperatures (up to 200 °C) without concentration, cutting out both convective and conductive thermal losses of the internal gas. The system losses are mainly due to the radiative energy emitted by the absorber. In this paper, a power balance equation has been used to perform the best fit of the data recorded with the absorber first exposed to the Sun illumination (up to the stagnation temperature, typically above 300 °C) and then cooled down by using an opaque shield. In particular, the fitting procedure is useful to evaluate the spectrally averaged absorptivity and the temperature dependent spectrally averaged emissivity of the absorber in a realistic operating condition.